ANALISIS BIAYA DIFERENSIAL DALAM PENGAMBILAN KEPUTUSAN MENERIMA ATAU MENOLAK PESANAN KHUSUS PADA UD. SANTIA DEKOR - Salsabila, Talitha; Pebiana, Santi; Sari, Dian Puji Puspita (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
Presentation of accurate information is the main requirement to assist management in making decisions and choosing alternatives as the best course of action among alternatives. Differential accounting information consists of costs, income, and assets. This study takes the object of UD. Santia Decoration in the field of decoration (curtains and wallpapper). This research uses descriptive quantitative research with existing data sources. Results of analysis of calculations using differential accounting information in decision making to reject or accept special orders.